Epidemiology and Regional Programs on Meningococcal Disease Prevention in Tyumen Region and Yamalo-Nenets Autonomous District - Olga A. Richkova; Ludmila A. Nechepurenko; Maria M. Sheshegova; Ksenia P. Kuzmicheva; Natalia E. Gorokhova; Galina V. Sharukho; Luydmila V. Khanipova; Darya D. Bekina; О. А. Рычкова; Л. А. Нечепуренко; М. М. Шешегова; К. П. Кузьмичева; et al. (Current Pediatrics, 2020)
Meningococcal disease is the urgent problem of healthcare due to its widespread prevalence, high incidence, severe course and high risk of mortality. Vaccination of Russian Federation population with polyvalent meningococcal vaccine for serogroups A, C, W, Y has not been studied before within the framework of regional immunization programs. The article presents the results of epidemiological analysis of the situation on meningococcal disease in Tyumen region and Yamalo-Nenets autonomous district (YNAD) in 2014-2019. The obtained data were used to develop the immunization strategy against meningococcal disease within the framework of the regional immunization calendar in Tyumen region and regional immunization programs in YNAD. The clinical case of severe course of meningococcemia with complications is presented in the article. Clinical conditions and syndromes which are common for practice of therapists during the management of patients with generalized forms of meningococcal disease are described. Менингококковая инфекция является актуальной проблемой здравоохранения в связи с повсеместным распространением, сохраняющейся высокой заболеваемостью, тяжелым течением и высоким риском летального исхода. Вакцинация населения Российской Федерации поливалентной вакциной к менингококкам серогрупп A, C, W, Y в рамках региональных программ иммунизации ранее не изучалась. В статье приведены результаты эпидемиологического анализа ситуации по менингококковой инфекции в Тюменской области и Ямало-Ненецком автономном округе (ЯНАО) в 2014-2019 гг. Полученные данные были использованы для разработки стратегии иммунизации против менингококковой инфекции в рамках регионального календаря прививок в Тюменской области и региональных программ иммунизации в ЯНАО. Представлен клинический случай тяжелого течения менингококкемии с осложнениями, описаны клинические состояния и синдромы, с которыми сталкиваются врачи-интернисты при терапии пациентов с генерализованными формами менингококковой инфекции.